2021
DOI: 10.54690/margallapapers.25.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Rise of China: Growing Strategic Competition Between the Us and China

Abstract: The emergence of China as a great power is indubitably one of the greatest perplexities in the international arena since the cold war era. Similarly, it poses challenges to the strategic position of the US. The economic and technological height of China has now become a big question mark for the US hegemony. The US has adopted some essential policies and actions like the B3W initiative and Strategic Competition Act of 2021, which label China a strategic competitor in multiple areas, including economics, techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The following principles were considered for establishing the index system: scientific and objective principles, concise and systematic principles, feasible and comparable principles, representative and oriented principles, and purposeful and dynamic principles. Starting from the essence and influencing factors of provincial development of the NEV industry, referring to the mentioned research literature, we built a comprehensive evaluation index system from four dimensions: social and economic, technology, new energy vehicle, and carbon neutralization [29][30][31][32].…”
Section: Index Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The following principles were considered for establishing the index system: scientific and objective principles, concise and systematic principles, feasible and comparable principles, representative and oriented principles, and purposeful and dynamic principles. Starting from the essence and influencing factors of provincial development of the NEV industry, referring to the mentioned research literature, we built a comprehensive evaluation index system from four dimensions: social and economic, technology, new energy vehicle, and carbon neutralization [29][30][31][32].…”
Section: Index Systemmentioning
confidence: 99%
“…Zheng et al found that China's new energy vehicle business ecosystem was gradually forming, but it was highly dependent on policies, and self-development ability needs to be improved [29]. In the aspect of the evaluation indicator system, Bai et al analyzed the competition in the global electric vehicle industry from the following dimensions: core technological innovation capability, the openness of the EV market, policy support, industrial scale, market size, and overall policy effects [30]. Cao et al proposed the stakeholder engagement system to analyze the commitments and efforts needed from multiple stakeholders through policy implications, leading factors on the demand side, and technology innovation requirements on the supply side [31].…”
Section: Introductionmentioning
confidence: 99%
“…Academic perspectives view China's international discourse system as contextually specific within certain socio-cultural frameworks, representing a unique mode of globally articulating China's concepts, perspectives, and expertise (Ali, 2022). This discourse system is a meaningful exercise in interpreting the road of socialism with Chinese characteristics, in telling Chinese story, in shaping national identity and in constructing discursive power on the global stage.…”
Section: Introductionmentioning
confidence: 99%